The Penal Effects of Cryptocurrencies on Monetary Policy - Fadel Hamoudi Abd , Researcher. Nabaa; Omar Muslim Salman Al-Khaldi, Assist. Prof. Asil (Basra studies journal, 2023)
Sharif The prominent shift in this field is the issuance of cryptocurrencies through electronic programming, where payment is made directly through peer-to-peer transactions. The expansion of modern electronic technologies, the multitude of relevant entities, and the diversity of policies and goals have led to a lack of clarity in vision and effective coordination among the involved parties due to the differences in their technical domains. This makes criminal protection difficult to define and establish. Thus, it is necessary to restrict the principles of currencies, specify the conditions for dealing with them, and determine their risks on the national economy and the monetary policy of the state. Despite official warnings about dealing with these innovations due to the risks they entail and their insecure use, such as money laundering and terrorism financing, this calls for the establishment of a legal regulatory system to criminalize dealing with these currencies in case of violation of specific legal provisions and to minimize their risks as much as possible.